Case, travel, socioeconomic and meteorological data for analysing socioeconomic and environmental patterns behind H1N1 spreading in Sweden - Bota, András; Holmberg, Martin; Gardner, Lauren; Rosvall, Martin (Umeå University, 2021)
Collection of socio-economic and meteorological indicators as well as travel patterns and cases of H1N1 during the swine flu pandemic in Sweden in 2009. Comprise the supplementary information for the paper titled "Socioeconomic and environmental patterns behind H1N1 spreading in Sweden" by András Bóta, Martin Holmberg, Lauren Gardner and Martin Rosvall, Sci Rep 11, 22512 (2021). https://doi.org/10.1038/s41598-021-01857-4
Identifying the critical socio-economic, travel and climate factors related to influenza spreading is critical to the prediction and mitigation of epidemics. In the paper we study the 2009 A(H1N1) outbreak in the municipalities of Sweden, following it for six years between 2009 and 2015. Our goal is to discover the relationship between the above indicators and the timing of the epidemic onset of the disease. We also identify the municipalities playing a key role in the outbreak as well as the most critical travel routes of the country.

Publication available at: https://doi.org/10.1038/s41598-021-01857-4

Municipality codes for the municipalities of Sweden can be found here:
https://www.scb.se/en/finding-statistics/regional-statistics/regional-divisions/counties-and-municipalities/counties-and-municipalities-in-numerical-order/

Data available according to Creative Commons Attribution-NonCommercial 4.0 International (CC BY-NC 4.0) license

Model inputs
1. giim_kommun_graph.csv
Set of frequent travel routes between the municipalities of Sweden.
The graph was constructed from "Trafikanalys, 2016. Resvanor. (accessed 26.8.19). Available from: http://www.trafa.se/RVU-Sverige/." using the methodology described in the paper.
Date of construction: 2018-12-01
Format: csv
Structure: edge list in (kommun1;kommun2) format with rows indicating a directed link between two municipalities. Municipalities are denoted according to their official municipal code

2. giim_casecounts.xlsx
Number of new H1N1 cases in the municipalities of Sweden between 2009 and 2015.
Our data set consists of all laboratory-verified cases of A(H1N1)pdm09 between May 2009 and December 2015, extracted
from the SmiNet register of notifiable diseases, held by the Public Health Agency of Sweden.
Due to confidentiality reasons, cases are anonymized, and addresses are aggregated at the DeSo level together with
the date of diagnosis, age, and gender. We obtained ethical approval for the data acquisition.
Date of construction: 2018-12-01
Format: xlsx
Structure: Each tab represents a single flu season from the 2009/2010 season to the 2014/2015 season.
Each tab is a matrix with rows indicating municipalities according to their official municipal code, and columns indicating epidemic weeks. Values of the matrices indicate the number of new laboratory-verified cases of A(H1N1)pdm09

3. giim_kommun_indicators.csv
Socioeconomic and meteorological indicators are assigned to the municipalities of Sweden according to the methodology described in the paper.
Indicators included are:
a, mean temperature in degree Celsius,
b, absolute humidity in grams per cubic metre,
c, population size as the number of people living in each municipality,
d, population density as the number of people per sq. km of land area,
e, median income per household in thousand SEK,
f, fraction of people on social aid (as a percentage),
g, average number of children younger than 18 years per household.
Meteorological data was obtained from the European Climate Assessment Dataset "Klein Tank A, Wijngaard J, Können G, Böhm R, Demarée G, Gocheva A, et al. Daily dataset of 20th-century surface
air temperature and precipitation series for the European Climate Assessment. International Journal of Climatology: A Journal of the Royal Meteorological Society. 2002;22(12):1441–1453."
Data from the dataset was converted to the municipality level according to the methodology described in the paper. Variables are mean temperature and relative humidity converted to absolute humidity
for all municipalities of Sweden.
Socioeconomic data was collected from Statistics Sweden between 2018 Ocotber and 2019 February. Available from: https://www.scb.se/en/. Variables are: The average household income
as an economic indicator. The average number of children younger than 18 years per household to indicate family size.
The fraction of people receiving social aid to represent poverty in a municipality. Population size and population density as the number of people per sq. km of land area.
Date of construction: 2018-02-01
Format: csv
Structure:
Each row corresponds to a municipality denoted according to their official municipal code. Columns indicate socioeconomic and meteorological indicators as marked by the header row.

Model outputs
1. giim_export_risk.csv
Exportation risk values for all municipalities from week 37 to week 50 in the fall of 2009 computed using the methodology described in the paper.
Date of construction: 2020-12-01
Format: csv
Structure: Table with rows denoting Swedish municipalities according to their official municipal code, columns denoting epidemic weeks. Values indicate exportation risk values (should not be interpreted as probabilities).

2. giim_import_risk.csv
Importation risk values for all municipalities from week 37 to week 50 in the fall of 2009 computed using the methodology described in the paper.
Date of construction: 2020-12-01
Format: csv
Structure: Table with rows denoting Swedish municipalities according to their official municipal code, columns denoting epidemic weeks. Values indicate importation risk values (should not be interpreted as probabilities).

3. giim_transmission_prob.csv
Transmission probabilities between all municipalities from week 37 to week 50 in the fall of 2009 computed using the methodology described in the paper.
Date of construction: 2020-12-01
Format: csv
Structure: Edge list with multiple edge weights. Rows indicate a directed link between the two municipalities (kommun1;kommun2) in the beginning of the row. The rest of the values in each row denote
the corresponding transmission probabilities for each epidemic week computed according to the methodology described in the paper.

Samling socioekonomiska och meterologiska indikatorer samt resemönster och fall av H1N1 under svininfluensapandemin i Sverige under 2009. Utgör kompletterande information för artikeln "Socioeconomic and environmental patterns behind H1N1 spreading in Sweden" by András Bóta, Martin Holmberg, Lauren Gardner and Martin Rosvall, Sci Rep 11, 22512 (2021). https://doi.org/10.1038/s41598-021-01857-4
Att identifiera de kritiska socioekonomiska, rese- och klimatfaktorerna som rör spridning av influensa är avgörande för att förutsäga och mildra epidemier. I artikeln studerar vi 2009 A (H1N1)-utbrottet i Sveriges kommuner under sex år mellan 2009 och 2015. Vårt mål är att upptäcka sambandet mellan ovanstående indikatorer och tidpunkten för sjukdomsepidemin. Vi identifierar också kommunerna som spelar en nyckelroll i utbrottet, liksom de mest kritiska resvägarna i landet.

Artikel tillgänglig på https://doi.org/10.1038/s41598-021-01857-4

Kommunkoder för Sveriges kommuner hittar du här:
https://www.scb.se/en/finding-statistics/regional-statistics/regional-divisions/counties-and-municipalities/counties-and-municipalities-in-numerical-order/

Data tillgänglig enligt Creative Commons Erkännande-IckeKommersiell 4.0 Internationell (CC BY-NC 4.0)-licens.

Delade filer
Modellinput
1. giim_kommun_graph.csv
Uppsättning av frekventa resvägar mellan Sveriges kommuner.
Diagrammet är konstruerat från "Trafikanalys, 2016. Resvanor. (Nedladdat 26.8.19). Tillgänglig från: http://www.trafa.se/RVU-Sverige/." med hjälp av den metod som beskrivs i artikeln.
Sammaställningsdatum: 2018-12-01
Format: csv
Struktur: kantlista i (kommun1; kommun2) format med rader som indikerar en riktad länk mellan två kommuner. Kommuner betecknas enligt deras officiella kommunalkod

2. giim_casecounts.xlsx
Antal nya H1N1 -fall i Sveriges kommuner mellan 2009 och 2015.
Vårt dataset består av alla laboratorieverifierade fall av A (H1N1) pdm09 mellan maj 2009 och december 2015, extraherade från SmiNet-registret över anmälningspliktiga sjukdomar, som finns hos Folkhälsomyndigheten.
Av sekretessskäl anonymiseras ärenden och adresser aggregeras på DeSo-nivå tillsammans med
datum för diagnos, ålder och kön. Vi fick etiskt godkännande för datainsamlingen.
Sammaställningsdatum: 2018-12-01
Format: xlsx
Struktur: Varje flik representerar en influensasäsong från säsongen 2009/2010 till säsongen 2014/2015.
Varje flik är en matris med rader som anger kommuner enligt deras officiella kommunala kod och kolumner som anger epidemiska veckor. Matrisernas värden indikerar antalet nya laboratorieverifierade fall av A (H1N1) pdm09

3. giim_kommun_indicators.csv
Socioekonomiska och meteorologiska indikatorer tilldelade Sveriges kommuner enligt den metod som beskrivs i artikeln.
Indikatorer som ingår är:
a, medeltemperatur i grader Celsius,
b, absolut luftfuktighet i gram per kubikmeter,
c, befolkningsstorlek som antalet personer som bor i varje kommun,
d, befolkningstäthet som antalet personer per kvadratkilometer landyta,
e, medianinkomst per hushåll i tusen SEK,
f, andelen personer som får socialbidrag (i procent),
g, genomsnittligt antal barn yngre än 18 år per hushåll.
Meteorologiska data erhölls från European Climate Assessment Dataset "Klein Tank A, Wijngaard J, Können G, Böhm R, Demarée G, Gocheva A, et al. Daglig data av 1900-talets ytlufttemperatur och nederbördsserier för den europeiska klimatbedömningen. International Journal of Climatology: A Journal of the Royal Meteorological Society. 2002; 22 (12): 1441–1453. "
Data konverterades till kommunnivå enligt den metod som beskrivs i artikeln. Variabler är medeltemperatur och relativ luftfuktighet omvandlad till absolut fuktighet för alla kommuner i Sverige.
Socioekonomiska data samlades in från SCB mellan 2018 Ocotber och 2019 februari. Tillgängliga från: https://www.scb.se/en/. Variabler är: Den genomsnittliga hushållsinkomsten som en ekonomisk indikator. Det genomsnittliga antalet barn yngre än 18 år per hushåll för att ange familjens storlek.
Andelen människor som får socialhjälp för att representera fattigdom i en kommun. Befolkningens storlek och befolkningstäthet som antalet personer per kvadratkilometer landyta.
Sammaställningsdatum: 2018-02-01
Format: csv
Struktur:
Varje rad motsvarar en kommun betecknad enligt deras officiella kommunal kod. Kolumner anger socioekonomiska och meteorologiska indikatorer som markeras med rubrikraden.

Modelloutput
1. giim_export_risk.csv
Exportriskvärden för alla kommuner från vecka 37 till vecka 50 hösten 2009 beräknas med hjälp av den metod som beskrivs i artikeln.
Sammaställningsdatum: 2020-12-01
Format: csv
Struktur: Tabell med rader som anger svenska kommuner enligt deras officiella kommunkod, kolumner som anger epidemiveckor. Värden indikerar exportriskvärden (ska inte tolkas som sannolikheter).

2. giim_import_risk.csv
Importriskvärden för alla kommuner från vecka 37 till vecka 50 hösten 2009 beräknas med hjälp av den metod som beskrivs i artikeln.
Sammaställningsdatum: 2020-12-01
Format: csv
Struktur: Tabell med rader som anger svenska kommuner enligt deras officiella kommunkod, kolumner som anger epidemiveckor. Värden indikerar importriskvärden (ska inte tolkas som sannolikheter).

3. giim_transmission_prob.csv
Sändningssannolikheter mellan alla kommuner från vecka 37 till vecka 50 hösten 2009 beräknades med hjälp av den metod som beskrivs i artikeln.
Byggnadsdatum: 2020-12-01
Format: csv
Struktur: Länklista med flera länkvikter. Rader indikerar en riktad länk mellan de två kommunerna (kommun1; kommun2) i början av raden. Resten av värdena i varje rad betecknar motsvarande överföringssannolikheter för varje epidemivecka beräknad enligt den metod som beskrivs i artikeln.
Fall-, rese-, socioekonomisk och meterologisk data för att analysera socioekonomiska och miljömässiga mönster bakom spridningen av H1N1 i Sverige
Keywords: influenza; influensa; public health; folkhälsa; epidemiology; epidemiologi; network analysis; Socioeconomic factors; Socioekonomiska faktorer; Influensa A-virus, subtyp H1N1; Influenza A Virus, H1N1 Subtype; Pandemics; Pandemier; Temperature; temperatur; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Information technology; Informationsteknik; Computer Sciences; Datavetenskap (datalogi); Health; Hälsa; Public health; Folkhälsa; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin